Rationalized Toeplitz Hankel operators on the space of Torus L2(Tn) - Batra, Ruchika Verma (GANIT: Journal of Bangladesh Mathematical Society, 2024)
In this paper we introduce the class of Rationalized Toeplitz Hankel operators on the space L2(Tn), T being the unit circle in complex plane and L2(Tn) is the space of Lebesgue square integrable functions on Tn. We also introduce the Rationalized Toeplitz Hankel matrix of level n and give the characterization of Rationalized Toeplitz Hankel Operator. J. Bangladesh Math. Soc. 44.2 (2024) 039–046